2014
DOI: 10.1097/anc.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Managing Gastroesophageal Reflux Symptoms in the Very Low-Birth-Weight Infant Postdischarge

Abstract: Gastroesophageal reflux and gastroesophageal reflux disease symptoms are common challenges for very low-birth-weight infants (<1500 g). These symptoms frequently result in feeding difficulties and family stress. Management of symptoms across healthcare disciplines may not be based on current evidence, and inconsistency can result in confusion for families and delayed interventions. The feeding relationship between infant and caregivers may be impaired when symptoms are persistent and poorly managed. An algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
1
0
0
1
Order By: Relevance
“…The predictors of the performance of fundoplication remain unclear (1). GERD is more severe and frequent in premature infants, and our study confirmed that low birth weight is a predictor of GERD and the performance of antireflux surgery (16,17). Very low birth weight (VLBW; <1500 g) infants were recognized by Spitz in the early 1990s for having a lower survival rate (18,19).…”
Section: Discussionsupporting
confidence: 74%
“…The predictors of the performance of fundoplication remain unclear (1). GERD is more severe and frequent in premature infants, and our study confirmed that low birth weight is a predictor of GERD and the performance of antireflux surgery (16,17). Very low birth weight (VLBW; <1500 g) infants were recognized by Spitz in the early 1990s for having a lower survival rate (18,19).…”
Section: Discussionsupporting
confidence: 74%
“…Hal ini sesuai dengan penelitian oleh Cheema et al 5 bahwa BBLR ialah faktor risiko untuk RGE. Sherrow et al 14 juga menyatakan bahwa gejala RGE maupun PRGE umum ditemukan pada riwayat BBLR. Rerata kelompok kasus dan kelompok kontrol dalam penelitian ini sebesar 2575 (SD ± 532,5) gram dan 2778,3 (SD ± 550,3) gram.…”
Section: Bahasanunclassified